A constrained framework for context‐aware remote E‐healthcare (CARE) services. Issue 8 (17th June 2019) - Sharma, Ashutosh; Kumar, Rajiv
Abstract: Recently, due to the health awareness among the current generations, it leads us to give special attention to the remote E‐healthcare services. The remote E‐healthcare services have been categorized mainly into three categories: primary care, secondary care, and emergency care. Due to the categorized remote healthcare services, the resources must have to be utilized efficiently. Therefore, context‐aware modelling for the remote E‐healthcare (CARE) services has been used to save the resource wastage. The CARE services have been divided into three categories primary context‐aware remote E‐healthcare, secondary context‐aware remote E‐healthcare, and emergency context‐aware remote E‐healthcare (E‐CARE). Three different algorithms have been proposed for the performance analysis. The result shows that the proposed algorithms for the primary context‐aware remote E‐healthcare and secondary context‐aware remote E‐healthcare do not make more difference in the routing. However, the selection of the path for the E‐CARE shows that the hop count of the path has been increased. The increase in the hop count leads to an increase in energy efficiency and the life of the services. Additionally, observation made from our assigned algorithm E‐CARE shows that it performs extremely well for the E‐healthcare services without incrementing the time complexity. Furthermore, major characteristics of the algorithm has been explored and analyzed for the E‐healthcare services. Abstract : E‐healthcare services are categorised mainly into three categories: primary care (P‐CARE), secondary care (S‐CARE), and emergency care (E‐CARE). The result shows that the proposed algorithms for the P‐CARE and S‐CARE do not make more difference in the routing. However, the selection of the path for the E‐CARE shows that the hop count of the path has been increased which leads to an increase the time complexity. Further, major characteristics of the algorithm has been explored and analysed for the E‐healthcare services using comparative study with existing algorithms and average qualified service set (QSS).